Pengaruh Reward Terhadap Motivasi Kerja Pada Karyawan Badan Waqaf Al-Qur’an Cabang Yogyakarta - Farhan Pratama; Bangun Putra Prasetya (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to explain the influence of reward variables and partial motivation on employee performance. This research uses a quantitative method with the sample determination method used is Purposive Sampling with a sample size of 20 and collecting samples by distributing questionnaires. The data analysis used is descriptive statistical analysis. The results show the results of Validity analysis testing to determine the significance of the influence of rewards on work motivation. The table of questions regarding the influence of rewards on work motivation 1-6 above shows correlation values ​​of 0.738, 0.731, 0.665, 0.853, 0.678, 0.693, and the significant values ​​for the questions on the influence of rewards on work motivation 1-6 are 0.00 and 0.01, so it can be stated valid, and the results of the reliability statistics on the reward variable questions, the Cronbach's Alpha value is 0.654, this value exceeds the minimum value of 0.60, thus the questions in the reward variable table are declared reliable or reliable.